NPA Management: A Study of New Private Sector Banks in India - Khurana, Ashok; Singh, Mandeep (Indian Journal of Finance, 2010)
The Indian Banking Industry has played a pivotal role in the socio- economic augmentation of the country. The Financial Sector Reforms initiated in 1991 have commendably changed the visage of Indian Banking. The banking industry has transmogrified in a phased manner from a regulated environment to a deregulated market economy.The RBI has accorded its approbation for the inception of new banks in the private sector acting on the recommendations of the Narasimham Committee. The banking industry, which already enjoys a privileged status as far as public sector banks are concerned, have assumed a more aggressive and cut throat competitive position on account of establishment of private sector banking. A recent survey conducted by McKinsey&Co., in association with the Indian Banks Association, revealed that new private banks have a strong competitive advantage over public sector banks on several dimensions such as use of low cost technology and operations to address the urban mass market, alignment between IT and business heads, more focus on value adding activities, better talent management, superior complexity handling, and the ability to use infrastructure optimization facilities. In spite of efficiently managing their financial resources, akin to public sector banks, these new generation banks have also become a victim of Non Performing Assets (NPAs). A Non Performing Asset is an asset or account of borrower, which has been not been serviced by the borrower, and the bank has stated the same as sub-standard, doubtful or loss asset, as per the norms and directions of the RBI. Non-Performing Assets (NPA) have emerged as an alarming threat to the Indian banking industry and their reduction has become synonymous with professional functioning and management of banks. However, NPAs should not be seen as a dilemma but as a challenge for the banking sector. The global recession coupled with consequential slow down in the domestic markets had cast their shadow on the Indian banking sector, resulting in the growth in NPAs in absolute and relative terms since 2005-06. This evoked the researchers’ interest to conduct a research on the management of NPAs by the new private sector banks in India.